(FE)MALE MIND IN WOOLF’S ORLANDO - SHEREEN HUSSEIN HAMDAN, MOHD NAZRI LATIFFAZMI, HAMZEH ALI NAJADAT (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Currently, clashes among binaries in our lives are so many. One of them is male/female issues, especially in minds. The application of the Androgynous mind theory by Virginia Woolf on Orlando Novel for the same theorist is controversial between the researchers and critics. It has two sides, one is connected to the cognizance and the other one is connected to the physical side. This paper shed light on the mental part with feministic background and in access to psychoanalysis excluding the physical side. Some researchers interpret Orlando under the physical side of the Androgyny, while this paper shows that there is no connection between Virginia and her novel that some researchers, such as Rado, try to demonstrate the transsexual operations through literary works. On one hand, the Androgynous mind theory has been manipulated by some scholars for their interests or other agenda, such as Sandra Bem, who uses this theory to promote the idea of transgenderism. On the other hand, the Androgynous mind theory in connection with feminism and access to psychoanalysis can be beneficial for the societies apart from the physical side applications. To put it differently, it is a tool for thinking like a man and a woman at the same time. As a result, one, regardless of his/her gender, can get benefited from the theory in his/her daily basis when dealing with the other gender to understand and feel him/her.